From cell size and first principles to structure and function of unicellular plankton communities. (April 2023) - Andersen, K.H.; Visser, A.W.
Abstract: Here we review, synthesize, and analyse the size-based approach to model unicellular plankton cells and communities. We first review how cell size influences processes of the individual the cell: uptake of dissolved nutrients and dissolved organic carbon, phototrophy, phagotrophy, and metabolism. We parameterize processes primarily from first principles, using a synthesis of existing data only when needed, and show how these processes determine minimum and maximum cell size and limiting resource concentrations. The cell level processes scale directly up to the structure and function of the entire unicellular plankton ecosystem, from heterotrophic bacteria to zooplankton. Community structure is described by the size spectrum and by the emergent trophic strategies. We develop an analytical approximate solution of the size spectrum and show how the trophic strategies of osmotrophy, light- and nutrient-limited phototrophy, mixotrophy, and pure phagotrophy depend on the resource environment. We further develop expressions to quantify the functions of the plankton community: production, respiration, and carbon available to production of higher trophic levels, and show how the plankton community responds to changes in temperature and grazing from higher trophic levels. We finally discuss strengths and limitations of size-based representations of plankton communities and which additional trait axes will improve the description of plankton functional diversity. Highlights: Plankton cell size determines affinities for diffusive uptake, light harvesting, and phagotrophy. Closed-form solutions for the biomass and limiting resources as functions of cell size. Analysis of community functions and efficiencies. Emergent temperature response of cell division rate.